Group Guidance using Rational Emotive Behavior Therapy Approach to Reduce Verbal Bullying - Nur Alfiah; Maskhur Maskhur; Muhamad Rifa'i Subhi; Moh Muslih (Program Studi BKPI IAIN Salatiga, 2022)
Having poor problem solving skills may cause someone to experience verbal bullying. Verbal bullying in adolescents can be manifested into several forms, for instance giving nicknames, reproaches, slander, cruel criticism, insults, gossip, ostracism, and so on. Therefore, the purpose of the study was to test the effectiveness of group guidance using the Rational Emotive Behavior Therapy (REBT) approach in reducing students' verbal bullying. The research used the first experimental design in Pre-Experimental Design (non-design), namely One-Group Pretest-Posttest Design, which involved 16 students of MAN 2 Pekalongan. Data were collected using a verbal bullying behavior scale (r1=0.367-0.0650 =0.807), questionnaires, observations, and interviews. The data was then analysed using Wilcoxon signed ranks test. The results of the study showed that there were differences in their verbal bullying behavior (research subjects) after given the group guidance services, with Z = -2,358 and p-value = 0.018 (p = value 0.050). This indicates that group guidance using the REBT approach can reduce students' verbal bullying, so that the group guidance model using the REBT approach can be used to develop students' positive behavior.